2015
DOI: 10.1007/s11695-015-1958-2
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Intraoperative Endoscopy May Decrease Postoperative Stenosis in Laparoscopic Sleeve Gastrectomy

Abstract: Routine use of IOE in LSG has led to a change in the operative strategy and could be one of the reasons behind the acceptable leak and stenosis in this series of laparoscopic sleeve gastrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Presence of obstruction increases the risk of leakage post operatively. 9 While it is difficult to assess the presence of a stenosis at the incisura laparoscopically, this can easily be detected using intra operative endoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Presence of obstruction increases the risk of leakage post operatively. 9 While it is difficult to assess the presence of a stenosis at the incisura laparoscopically, this can easily be detected using intra operative endoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Nimeri et al performed IOE during LSG and found 10 cases (3.2%) of gastric stenosis during the procedure. Stenosis resolved after removing over-sewing sutures and clinical stenosis after LSG was 0% [ 20 ]. As shown in the present study, IOE can guide the surgeons to check the cause and location of stenosis with revision performed laparoscopically.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they stated that suturing the staple line was also a disadvantage in terms of bleeding. 12 This may be related to the level of experience with the suturing technique. The bleeding rate of 0.55% in our study is still low compared with the literature.…”
Section: Discussionmentioning
confidence: 99%